The Concept of Political Success: Reflections on Leftist Politics of Sindh - Dr. Amjad Ali Channar (Journal of Research in Social Sciences, 2025)
Success in politics plays a crucial role in today’s democratic societies. A political party is considered successful when it wins elections and assumes control of the government. The primary factors that determine political success generally include the party's voter base, organizational strength, cohesive narrative, political vision, resource mobilization, and policies that resonate with the socio-economic and religious context of the country. Left-wing parties in Sindh struggled with these critical components, failing to meet the established standards of political success. This paper examines the concept of political success through a critical study of Sindh’s leftist parties, utilizing qualitative methods and scholarly sources. Thie key findings of this paper demonstrate that left-wing parties fail to meet essential benchmarks of political success, including organizational structure, popular narrative, and electoral performance, leading to their irreversible decline